Digital Transformation and the Changing World of Work (DiWaBe 2.0): A Data Source for Research on Artificial Intelligence and Other Technologies in the Workplace - Arntz, Melanie [Verfasser]; Baum, Myriam [Verfasser]; Dorau, Ralf [Verfasser]; Hartwig, Matthias [Verfasser]; Lehmer, Florian [Verfasser]; Arntz, Melanie [Verfasser] Baum, Myriam [Verfasser] Dorau, Ralf [Verfasser] Hartwig, Matthias [Verfasser] Lehmer, Florian [Verfasser] Matthes, Britta [Verfasser]; Meyer, Sophie-Charlotte [Verfasser]; Schlenker, Oliver [Verfasser]; Tisch, Anita [Verfasser]; Wischniewski, Sascha [Verfasser] (Bundesanstalt für Arbeitsschutz und Arbeitsmedizin, 2025)
"In Germany, more than half of employees are already using artificial intelligence (AI) in the workplace, although the majority do so informally. This suggests that employees perceive AI applications as supportive tools, yet it also highlights that firms are falling behind employees’ expectations regarding formalAI implementation. This report presents findings from the DiWaBe 2.0 survey, a representative cross-sectional survey conducted in 2024, covering approximately 9,800 employees subject to social insurance contributions in Germany. The survey aims to provide a database for evaluating the impact of technological change - particularly AI - on the workplace. It specifically focuses on changes in job tasks and skill requirements, working conditions and organizational structures, participation in continuing training, and employee health. The results indicate that the use of AI varies substantially by individual and occupational characteristics such as occupational segment, education, age, and gender. While only about one-third of employees without formal educational qualifications use AI, nearly 80% of employees holding university degrees or advanced vocational qualifications (Meister or Techniker) do so. Initial multivariate analyses show that employees who have intensified their AI usage over the past five years report higher complexity in their job tasks, especially in the areas of writing, programming, and mathematics. Furthermore, Intensified AI Use correlates with increased job autonomy but also with higher work intensity. However, no statistically significant correlation between AI usage and employee health was found. Moreover, there are no differences between AI users and non-users regarding their participation in continuing training activities." (Author's abstract ; BIBB-Doku)
Digital Transformation and the Changing World of Work (DiWaBe 2.0): A Data Source for Research on Artificial Intelligence and Other Technologies in the Workplace
Keywords: G 2.2.1 Technologisierung; G 1.2 Arbeitsmarkt; 370; 300; Künstliche Intelligenz; Arbeitsmarktentwicklung; Technische Entwicklung; Digitalisierung; Arbeitsanforderungen; Weiterbildung; Gesundheit